Mosaic Tetrasomy 13q and Phylloid Hypomelanosis: A Case Report and Review of the Literature. Issue 2 (12th June 2014) - Myers, Joseph N.; Davis, Loretta; Sheehan, Daniel; Kulharya, Anita S.
Abstract: A 6‐year‐old girl presented for evaluation of skin discoloration. Examination revealed oval and oblong hypopigmented macules on her trunk and extremities. Cytogenetic studies and immunohistochemistry of biopsies from normally pigmented and hypopigmented skin revealed mosaicism for partial tetrasomy for 13q with low melanocyte levels in lesional skin. The patient was diagnosed with phylloid hypomelanosis (PH), a distinct clinical entity linked to abnormalities in chromosome 13. This article reviews the literature regarding PH and supports the notion that mosaicism of the melanocyte region of chromosome 13q is responsible for PH.